Penerapan Manajemen Kelas Dalam Meningkatkan Hasil Belajar Ipa Siswa Kelas III Sd Negeri 4 Mamben Daya - Ihwan, Ihwan (Lembaga Bale Literasi, 2023)
This research aims to determine the improvement in science learning outcomes through the implementation of Class Management in class III students at SD Negeri 4 Mamben Daya for the 2023/2024 academic year. This type of research is Classroom Action Research with 2 cycles and 4 stages, namely planning, implementation, observation and reflection. The research subjects were 23 students in class III of SD Negeri 4 Mamben Daya, consisting of 11 boys and 12 girls. The data collection techniques used in this research are observation, tests and documentation. Data analysis used in this research is by using the classical percentage formula. The results of this research show that the results of the evaluation using written tests in the form of essays to determine student learning outcomes are quite good, namely from pre-cycle, cycle I to cycle II there has been an increase, namely in pre-cycle an average score of 60.21 was obtained with classical completeness of 39%. In cycle I, the average score increased by 66.47 with classical completeness of 65%, whereas in cycle II there was an increase with an average score of 81.6 with classical completeness of 87%. In this way, the implementation of Class Management can improve the science learning outcomes of Class III students at SD Negeri 4 Mamben Daya for the 2023/2024 academic year, which can be seen from the increase in the number of students who get learning outcomes above the KKM. This cannot be separated from the use of appropriate learning models and is very popular with students.